1992
DOI: 10.1177/07399863920143004
|View full text |Cite
|
Sign up to set email alerts
|

Chicana College Students on the Texas-Mexico Border: Tradition and Transformation

Abstract: In interviews with a probability sample of 218 Mexican-American women university students, the authors found that the number of hours Chicanas work weekly is vastly more important than either their connection to the ethnic community or their challenge to gender relations in terms of the time it takes them to earn a baccalaureate degree. The findings-both descriptive and multivariate-suggest that institutional responsiveness to their combined student/worker status is critical to their educational "success. "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Research also indicated that in addition to playing a supportive role, Mexican American mothers are influencing their daughters' academic pursuits by modeling behaviors. Having a mother with a college education was a significant predictor in the likelihood of Latinas to attend college (Cardoza, 1991) and in the amount of time it took Mexican American women to complete college (Young, 1992). In summary, Mexican American mothers are instrumental in the lives and academic pursuits of their daughters.…”
Section: Mentors' Influence On Mexican Americanmentioning
confidence: 97%
“…Research also indicated that in addition to playing a supportive role, Mexican American mothers are influencing their daughters' academic pursuits by modeling behaviors. Having a mother with a college education was a significant predictor in the likelihood of Latinas to attend college (Cardoza, 1991) and in the amount of time it took Mexican American women to complete college (Young, 1992). In summary, Mexican American mothers are instrumental in the lives and academic pursuits of their daughters.…”
Section: Mentors' Influence On Mexican Americanmentioning
confidence: 97%
“…Research upon Latinas' experience in higher education shows that family ties and obligations, male privilege, and higher education institutional structures often act as barriers to Latinas enrolling in college and completing a baccalaureate degree (Gandara, 1982;Cuadraz, 1996;Delgado Bernal, 1998). Latina college students coming from traditional households are expected to fulfill familial obligations regardless of college demands (Young, 1992;Sy & Romero, 2008). The traditional Hispanic family structure makes it incumbent upon Latinas to provide childcare for younger family members and engage in household domestic errands that Hispanic men are exonerated from (Gandara, 1995;Valenzuela, 1999;Sy & Romero, 2008).…”
Section: Latina Role Conflict: Gender-coded and Student Responsibilitiesmentioning
confidence: 99%
“…Barriers that Latina students face before attending college often include lower socioeconomic status, inferior and overcrowded schools, lack of parental knowledge concerning secondary education, cultural stereotyping, and low expectations from high school administrators (Cardoza, 1991;Gándara & Osugi, 1994;Rodriguez et al, 2000). Obstacles while attending college for Latina students include family responsibilities, financial pressures, lack of mentors, and low expectations (Gándara & Osugi, 1994;Gloria et al, 2005;Rodriguez et al, 2000;Young, 1992).…”
mentioning
confidence: 99%
“…Latina college students also have to contend with the "good Latina woman" cultural stereotype, which requires them to prioritize family needs over their own (Espinoza, 2010, p. 319). They may experience stress attempting to meet their family's needs and finding time to complete their academic work because in Latino families, domestic responsibilities frequently burden daughters more than sons (Cardoza, 1991;Espinoza, 2010;Gloria & Castellanos, 2012;Rodriguez et al, 2000;Sy & Romero, 2008;Valenzuela, 1999;Young, 1992). Latina students also often face financial constraints and most must work to support themselves and their families (Sy, 2006;Sy & Romero, 2008;Young, 1992).…”
mentioning
confidence: 99%